STUDI LITERATUR SISTEMATIS TENTANG PENGARUH KONSUMSI ALKOHOL TERHADAP PENYAKIT LIVER KRONIK - hernando, wiowen izaaz; Hernanda, Pratika Yuhyi (Calvaria Medical Journal, 2024)
Introduction: Health issues occur worldwide, including chronic liver diseases, which are often caused by alcohol consumption. Excessive alcohol intake can lead to liver diseases, alcoholic hepatitis, hepatocellular carcinoma (HCC), fibrosis, and cirrhosis. This literature review aims to analyze the extent of the relationship between alcohol consumption and the occurrence of chronic liver diseases. The study uses a literature review method, collecting information related to alcohol consumption and chronic liver disease events. The data are then analyzed descriptively, drawing from national and international journals from the past ten years, as well as textbooks. Results: Alcohol consumption can increase the risk of liver cirrhosis by up to 10.23 times, 3.43 times for liver cancer (HCC), and 3.88 times for hepatitis. The highest mortality risk (HR) for fatty liver occurs in both men and women with alcohol consumption ≥70g/day. Conclusion: This literature study indicates a significant association between alcohol consumption and an increased risk of liver cirrhosis and liver cancer.